Governança e gestão orientadas para eficiência das contas de uma instituição federal de ensino - SOUZA, Jean Patrick da Costa (Universidade Federal do Pará, 2022)
Through this study, we sought to evaluate the influence of governance and management recommendations on the efficiency of the public accounts of a Federal Education Institute. For this purpose, we developed an exploratory research with mostly qualitative approach, based on analysis of multiple sources of evidence, wich we obtained through a case study at the Federal Rural University of Amazon (UFRA). For this, we selected and presented the main practices of governance and management, according to Federal Court of Accounts recommendations; as well as the Key Performance Indicators able to define efficiency of an institution's public finances. Based on these instruments, we conducted individual analyses about the rate of acceptance of governance and management recommendations, also about the performance obtained by the accounts of the Institution it was examined, for the years 2017 and 2018. When we compared the results achieved by UFRA, we concluded that the efficiency of the institution's budgetary and financial accounts can be achieved by compliance with the governance and management recommendations about the themes of planning, risk management, internal control, integrity and accountability. With these results, we were able to submit a proposal for guidelines with main recommendations about governance and management that are capable of improve efficiency of the public accounts of the institution examined.